White collar crime predispositions among public groups in Malaysia - A/L Durairaja, Shankar (2020)
White collar crime can be labelled as a unique kind of crime because of the absence of any type of physical violence. The focus area of this criminology research is to study the predispositions of white collar crime among public groups in Malaysia. This study was based on criminological and psychological perspectives. The main aim of this study was to investigate the psychological, strain, and criminogenic characteristics that can lead to white collar crime among public groups in Malaysia. Five specific objectives were formulated. This study was divided into three stages. Firstly, to obtain epidemiological knowledge related to the main study trend analyses were performed to explore and document the trends and patterns of commercial crimes in Malaysia for the period of 18 years (2001-2018) and corruption for the period of seven years (2012-2018). Secondly, a validation study was conducted to test the compatibility, validity, and reliability of the items were tested in the Malay WCC Predispositions Battery (M-WCCPB) which consists of Malay translated 16 Personality Factors Questionnaire (16PF), Psychological Inventory of Criminal Thinking Styles (PICTS), Triarchic Psychopathy Measure (TriPM), and Chronic Stress Scale (CSS). Lastly, the main study was conducted by utilising a descriptive quantitative method that made use of the deductive approach based on the positivist philosophy. A guided self-administered psychometric battery (Malay WCCP Battery (M-WCCPB)) was employed for data collection. The M-WCCPB consisted of sociodemographic variables, and four Malay validated psychometric instruments. Thetotal of 274 white collar professionals and blue collar workers were recruited in this study through purposive sampling. Quantitative data were analysed using descriptive and inferential statistics. Out of 28 subdomains, only ten subdomains recorded significant differences. The association of selected traits representing Domain A (Personality Traits) and Domain B (Criminal Thinking Styles) and Domain C (Psychopathic Traits) appear to be pertinent for BCW, however these same straits were shown not to be significantly associated with either Domain B or Domain C in the WCP group. The present study only able to recruit 274 white collar professionals and bluecollar workers as the sample of study due to few limitations, therefore it was not meant to generalise the results to the working population in Malaysia. However, the significant findings of this study can be adapted by policymakers, and many governments and non-government agencies to design a better evidenced based hiring practices, and proactive white collar or commercial crime prevention.